Redefining the nasal septal L‐strut: A quantitative analysis of septal arcs and angles. (14th March 2018) - Han, Peter S.; Liu, Yuan F.; Messinger, Kelton; Ardeshirpour, Farhad; Inman, Jared C.
Abstract : Objective: To define and quantify common points and relationships within the anterior nasal septum and recognize the anatomic curvature of the dorsal and caudal septum as arcs with certain rises. Study Design: Case series study. Methods: Forty cadaveric quadrangular cartilages were dissected. Points along the septum were defined and relationships measured. Angles that composed the anterior septum using values that did account for the curvature of the anterior nasal septum, or classical L‐strut values, were compared to C‐strut values, which included rises away from the L‐strut. Results: The mean arc of the nasal septum dorsum was significantly longer than the caudal arc (25.9 ± 5.14 mm vs. 23.96 ± 4.07 mm, P = 0.048); the mean rise of the dorsal arc was significantly shorter than the rise of the caudal arc (3.04 ± 1.25 mm vs. 3.88 ± 1.42 mm, P = 0.006). The mean point of furthest rise of the dorsal arc was slightly anterior to the midpoint of the dorsal strut (13.43 ± 5.07 mm); the mean caudal equivalent was slightly posterior to the midpoint of the caudal strut (8.55 ± 4.33 mm). Septal angles measured using L‐strut versus C‐strut values were significantly different. Conclusion: The L‐strut leading edge is not congruent with the anatomic septum and can be better described as a C‐strut with arcs and rises away from classically interpreted straight L‐strut lines, all of which may guide surgeons in the creation of a more natural, supportive cartilage framework while encouraging quantifiable septorhinoplasty teaching. Level of Evidence: NA. Laryngoscope, 1806–1810, 2018